Prepričanja vzgojiteljev o rabi slikanice brez besedila v vrtcu - Skubic, Darija (Jezik in slovstvo, 2018)
Numerous research studies emphasise the importance of picture books for preschool children when developing literacy skills. The role of illustrations as an aid to help children visualise the literary content, understand the text and increase their vocabulary and verbalisation also receives attention in various studies. The main aim of the present study was to investigate preschool teachers' beliefs about wordless picture books and their use in kindergarten. For this purpose, an 18-item questionnaire was created and sent to randomly selected Slovenian kindergartens. A total of 175 respondents participated in the study. The results show that the attitude of preschool teachers towards wordless picture books and their use is positive and encouraging. The respondents did not differ significantly in their beliefs according to sex, age, education, working position and work experience, although some significant differences did emerge with regard to kindergarten locations.
Keywords: ankete; mnenja o uporabi slikanic brez besedila; slikanica brez besedila; slikanice; vrtci; vzgojitelji